Factors Associated With Hepatitis C Infection Among HIV-Infected Men Who Have Sex With Men With No Reported Injection Drug Use in New York City, 2000–2010. Issue 7 (July 2015) - Breskin, Alexander; Drobnik, Ann; Pathela, Preeti; Chan, Christine; Braunstein, Sarah; Bornschlegel, Katherine; Fuld, Jennifer
<x xml:space="preserve">Abstract</x> Background Hepatitis C (HCV) infection is a major source of morbidity and mortality among HIV-infected patients. Despite decreasing HCV incidence in the United States, the proportion of cases among men who have sex with men (MSM) without history of injection drug use (IDU) in New York City has more than tripled between 2000 and 2010. Methods Using matched surveillance data, we identified non-IDU HIV-infected MSM with and without diagnosed HCV. Differences in continuous variables were assessed with Mann-Whitney U tests, and Pearson χ2 tests were used for categorical variables. Poisson regression was used to compare HCV diagnosis rates by race/ethnicity and sexual transmitted disease history. Results There were 41, 303 non-IDU MSM diagnosed as having HIV before 2010 alive as of 2000, of whom 2016 (4.9%) were diagnosed as having HCV after HIV diagnosis. The HCV diagnosis rate was 605/100, 000 person-years. Adjusting for birth year and age at HIV diagnosis, Hispanics (rate ratio [RR], 1.4; 95% confidence interval [CI], 1.2–1.5) and non-Hispanic blacks (RR, 1.6; 95% CI, 1.4–1.8) had higher HCV diagnosis rates than did non-Hispanic whites. Adjusting for race/ethnicity, birth year, and age at HIV diagnosis, MSM diagnosed as having syphilis (RR, 2.5; 95% CI, 2.3–2.8) had higher HCV diagnosis rates than did those without syphilis. Conclusions We found a racial/ethnic disparity in HCV diagnosis rates and an association between HCV and syphilis, which is consistent with sexual transmission of HCV. With curative HCV treatment available, emphasis should be placed on adherence to guidelines recommending annual HCV screening for HIV-infected MSM, and education and outreach to MSM to prevent sexually transmitted HCV infections.